Staged approach to treating a patient with coronary artery disease and ventricular arrhythmias - E. A. Artyukhina; E. D. Strebkova; A. Sh. Revishvili (Российский кардиологический журнал, 2019)
The presented clinical case demonstrates an individual choice of a staged comprehensive approach to interventional treatment of a patient with coronary artery disease and ventricular tachyrhythmias, focused on myocardial revascularization and interventional abolition of ventricular tachyrhythmias.